2002
DOI: 10.1021/jp020558o
|View full text |Cite
|
Sign up to set email alerts
|

Electronic Gas-Phase Spectrum of the Pentaacetylene Cation

Abstract: The origin band of the A 2 Π u -X 2 Π g electronic transition of the linear pentaacetelyne cation, HC 10 H + , and isotopic derivatives, HC 10 D + and DC 10 D + , has been recorded in the gas phase. The absorption spectrum was observed by cavity ring down spectroscopy through a supersonic planar plasma expansion. The spectrum comprises both spin-orbit components with resolved P-and R-branches. Contour fits allow the determination of ground and excited state spectroscopic constants.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
20
0

Year Published

2004
2004
2014
2014

Publication Types

Select...
5
2

Relationship

0
7

Authors

Journals

citations
Cited by 18 publications
(20 citation statements)
references
References 16 publications
0
20
0
Order By: Relevance
“…7 This result is consistent with the polyacetylene cation series in which gas to Ne matrix shifts amounted to no greater than 1% of the transition's frequency. 17 The corresponding transition for the deuterated species, DC 8 D 2 + , is also shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 96%
“…7 This result is consistent with the polyacetylene cation series in which gas to Ne matrix shifts amounted to no greater than 1% of the transition's frequency. 17 The corresponding transition for the deuterated species, DC 8 D 2 + , is also shown in Fig. 1.…”
Section: Resultsmentioning
confidence: 96%
“…It has been suggested that the number of the cyanopolyynes, which have been detected in the space, amounts to 8 [6][7][8][9][10][11][12][13]. In addition, the linear cationic chains HC n H + (n = 4- 16) have also been extensively studied, both experimentally and theoretically, leading to reliable reference data about bond lengths, rotational constants, and absorption spectra for these species [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30][31][32].…”
Section: Introductionmentioning
confidence: 99%
“…The polyyne cations HC 2n H + , as representative for the open-shell carbon chain radicals, continue to be of special concerns [14][15][16][17][18][19][20][21][22][23][24][25][26][27][28][29][30]. Experimentally, Freivogel et al [16] and Dzhonson et al [24] measured the absorption spectra assigned as the A 2 u/g ← X 2 g/u transitions of HC 2n H + (n = 2-8) in 5 K neon matrices and in the gas phase, respectively.…”
Section: Introductionmentioning
confidence: 99%
“…[3][4][5][6][7][8] Those for n ) 10 and greater will have rotational constants on the order of 0.01 cm -1 or less, 8 thus creating difficulties in trying to elucidate the spectroscopic structure of these larger chains.…”
Section: Introductionmentioning
confidence: 99%